2018
DOI: 10.1002/ep.12948
|View full text |Cite
|
Sign up to set email alerts
|

D‐Galactose based hydrophobic ionic liquid: A new adsorbent for the removal of Cd2+ ions from aqueous solution

Abstract: The present study reports the synthesis of D‐galactose based hydrophobic ionic liquid (IL) and its potential application in the removal of Cd2+ ions from aqueous solution. The synthesized D‐galactose based hydrophobic ionic liquid is insoluble in water and stable at room temperature as a solid. Batch adsorption studies were carried out to investigate the sorption capacity of IL toward Cd2+ ions. The experimental data was analyzed with various isotherm and kinetic models to understand the adsorption process. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The first approach, developed by Jayachandra et al [ 21 , 22 , 23 ], and Kaur and Chopra [ 24 ], involved the selective protection of the secondary alcohols as acetals, the derivatization of the free primary hydroxyl functionality to obtain a good leaving group, and a final S N 2 reaction to give an ionic compound ( Scheme 1 ).…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The first approach, developed by Jayachandra et al [ 21 , 22 , 23 ], and Kaur and Chopra [ 24 ], involved the selective protection of the secondary alcohols as acetals, the derivatization of the free primary hydroxyl functionality to obtain a good leaving group, and a final S N 2 reaction to give an ionic compound ( Scheme 1 ).…”
Section: Synthesismentioning
confidence: 99%
“…The free primary hydroxyl group was then derivatized through an Appel reaction to give the corresponding iodide 3 [ 26 , 27 ]. Compound 3 was then reacted with a good nitrogen nucleophile (1-methylimidazole [ 21 , 22 , 23 ] or DABCO [ 24 ]) in an S N 2 fashion to give the desired ionic compound. This reaction is the weak point of the synthesis: It is very slow, and some days of heating under reflux were needed to obtain complete conversion and a good yield.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main takeaways from the use of CHILs in asymmetric chemistry is the necessity of free hydroxyl groups and hydrogen bonds for an effective chiral induction. On the other hand, in their articles from 2016 [ 67 ] and 2019 [ 68 ] the groups of Reddy and Lakshmipathy have shown that hydrophobic CHILs are effective adsorbents for the removal of Pb 2+ and Cd 2+ ion from aqueous solution.…”
Section: Application Of Chilsmentioning
confidence: 99%
“…Galactose based CHILs for the removal of Pd 2+ and Cd 2+ from aqueous solution by Reddy and Lakshmipathy et al [ 67,68 ] …”
Section: Application Of Chilsmentioning
confidence: 99%